2020
DOI: 10.1007/s00330-020-07563-5
|View full text |Cite
|
Sign up to set email alerts
|

Twin robotic x-ray system in small bone and joint trauma: impact of cone-beam computed tomography on treatment decisions

Abstract: Objectives Trauma evaluation of extremities can be challenging in conventional radiography. A multi-use x-ray system with cone-beam CT (CBCT) option facilitates ancillary 3-D imaging without repositioning. We assessed the clinical value of CBCT scans by analyzing the influence of additional findings on therapy. Methods Ninety-two patients underwent radiography and subsequent CBCT imaging with the twin robotic scanner (76 wrist/hand/finger and 16 ankle/foot/toe trauma scans). Reports by on-call radiologists be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
(48 reference statements)
0
28
0
1
Order By: Relevance
“…The other two studies were irrelevant and therefore not included [11,25]. Five studies were included in the paper [10,15,[17][18][19].…”
Section: Results Of Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The other two studies were irrelevant and therefore not included [11,25]. Five studies were included in the paper [10,15,[17][18][19].…”
Section: Results Of Searchmentioning
confidence: 99%
“…All patients included in the study underwent radiographs and CBCT. MRI scan is the gold standard imaging modality for radiocarpal fractures and was used on its own or in combination with clinical follow-up and surgical findings as a reference standard [10,15,[17][18][19].…”
Section: Reference Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Nardi et al identified an average dose of 7.1 µSv for CBCT scans of the appendicular skeleton, stating considerable dose reduction potential in comparison to multidetector CT imaging 22 . Compared to conventional radiography, however, radiation dose of CBCT remains significantly higher in most studies 23 . While scan protocols without a focus on dose reduction may have the potential to overcome the image quality of state-of-the-art multidetector CT scanners, we believe that CBCT can also challenge radiography as the primary method of fracture diagnosis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to distance to the radiation-sensitive body trunk, effective dose of extremity imaging is generally lower than for other body regions 25 . Providing diagnostic 3D image information with approximately four times the effective dose of standard 2D radiograms, the ultra-low-dose protocol in this study appears promising for primary use in particular imaging tasks, e.g., carpal bone 14 , 23 or radial head evaluation 26 . Furthermore, pediatric radiology could benefit from the reduced radiation dose in cases that require 3D assessment to ascertain the injury pattern, e.g., in distal humerus fractures 26 .…”
Section: Discussionmentioning
confidence: 99%